Sustainable Business Practices in the Defense Industry : Between Efficiency and National Security - Arief Prayitno (SEAN Institute, 2025)
Defense industry own role strategic in guard state sovereignty, but also faces challenge For apply practice business sustainable. Research This aiming For analyze balance between efficiency business and security national in implementation of sustainable business practices in the sector defense. With use approach qualitative, research This to study what is sustainability strategy can applied without sacrifice interest strategic state. Research results show that Implementation practice business sustainable in industry defense bring various benefits, such as efficiency cost, increase Power competition, innovation technology, and reduction impact environment. Implementation This allow industry defense operate more efficient through innovation technology friendly environment, diversification energy, and optimization chain supply. In addition, sustainability also helps industry face challenge geopolitics, regulation environment, and global market changes. Impact social seen from creation field Work quality as well as improvement welfare through development technology green and collaboration academic. However, there are necessary risks anticipated, such as dependence on technology foreign, threat cyber, and potential decrease readiness military consequence efficiency excessive. Therefore that, balance between efficiency business and needs strategic defense become crucial. Government and stakeholders interest need ensure that the sustainability strategy is implemented still support resilience national, guard independence technology, and improve readiness military in face future threats.